(untitled) (LACCEI, 2024)
The objective of this investigation is to evaluate the compressive strength of concrete f’c=175 kg/cm² with the addition of Whole Coffee Husks (WCH) and Ground Coffee Husks (GCH) in percentages 0.5%, 1.5% and 2.5 % with respect to the weight of the fine aggregate in the concrete mix. The investigation is of the experimental type with a quantitative approach, where a total of 63 units of standardized cylindrical concrete specimens are sampled. The instruments used for data collection were the formats established by the laboratory where the tests of the aggregates and concrete were carried out, for data analysis Excel spreadsheets were used. In the results it was obtained that the optimal addition is 0.5% in the case of the CCE and 1.5% in the case of the CCM, since they improve by 8.69% and 3. 68% respectively the compressive strength of concrete at 28 days of curing. On the other hand, the additions of 1.5% and 2.5% of CCE and 0.5% and 2.5% of CCM, generated a decrease in resistance of 12.45%, 23.42%, 13.98% and 29.59% respectively.